Genetic and Epigenetic Alterations Associated With Human Prenatal Tobacco and Environmental Tobacco Smoke Exposure: Protocol for a Systematic Evidence Map - Ana Teresa Reis; Ana Teresa Reis; Ana Teresa Reis; Joana Madureira; Joana Madureira; Joana Madureira; João Paulo Teixeira; João Paulo Teixeira; João Paulo Teixeira; Carla Costa; Carla Costa; Carla Costa (Public Health Reviews)
ObjectivesThis protocol outlines the development of a systematic evidence map (SEM) on genetic and epigenetic alterations associated with human prenatal tobacco exposure. The SEM will identify and synthetize epidemiological data on periconceptional and prenatal tobacco exposure associated with genetic (e.g., DNA damage) and epigenetic (e.g., DNA methylation) outcomes. Furthermore, it will describe the available evidence, highlight knowledge clusters, and identify gaps for future research.MethodsBibliographic databases and grey literature sources will be searched, complemented by reference mining. Predefined inclusion and exclusion criteria will guide study inclusion. Data extraction will include population, exposure, comparator, outcome, funding, study design, confounding factors, and statistical methods. Summarization will include a narrative review, graphical visualization, and an interactive, queryable and open-access table.ResultsA pilot study assessed the protocol’s feasibility, testing key components, including screening, data extraction, and eligibility criteria. Findings confirmed that the methodology is workable and reliable.ConclusionThis protocol supports a rigorous, reproducible, transparent SEM, aligned with international standards. The comprehensive mapping will support research prioritization and inform public health policies targeting maternal and child health.